A Study On The Suitability Of Task In Linked To The World3 With The Theory Of Communicative Competence Proposed By Celce Murcia - Widayati, Juli (2012)
This research paper elaborates the communicative competence developed within tasks presented in the textbook Linked to the World 3 viewed from the theory of communicative competence proposed by Celce Murcia. The objectives of the research are to analyze the communicative competence developed towards listening tasks, speaking tasks, reading tasks, writing tasks, and analyze to what extent the tasks in the textbook meet the criteria of communicative competence. This research belongs to a qualitative research. The data of the research are the tasks presented in the textbook Linked to the World 3. Whereas the data source is the textbook being researched, Linked to the World 3 written by F. A. Soeprapto and Mariana Darwis. The method to analyze the data is descriptive analysis. Having analyzed the textbook, the researcher comes to the conclusions as follows: the communicative competence developed in the listening task contains discourse competence and linguistic competence. The communicative competence developed within the speaking task covers all five aspects of communicative competence namely the discourse competence, linguistic competence, actional competence, strategic competence, and socio-cultural competence. The communicative competence developed in the reading task involves discourse competence, linguistic competence, and actional competence. Furthermore, the writing tasks of the textbook also give the students chance to build discourse competence, linguistic competence, and actional competence. Regarding the details of ommunicative competence developed within the four language skills, the textbook Linked to the World 3 has facilitated the development of communicative competence in good level.